Rapid generation of a sdhb loss-of-function zebrafish model for secreting pheochromocytomas and paragangliomas - S. Parisien-La Salle; F. Nobilleau; A. da Silva Babinet; J. Lamontagne; M. Labrecque; B. Rampal; C. Mas; M. Liao; V. A. Barragan Torres; G. Corbeil; L. Chatel-Chaix; M. Dona; et al. (npj Genomic Medicine)
Abstract Genotype plays a central role in the comprehensive management of pheochromocytomas and paragangliomas, highlighting the critical need for specific in vivo genetic models. Yet, animal models fall short of fully recapitulating the biological complexity of these tumours. We generated first-generation loss-of-function zebrafish models for sdhb, a canonical PPGL-associated gene, using CRISPR/Cas9. Sdhb-CRISPants exhibit increased heart rates, reduced swimming activity and premature death. In whole fish extracts, normetanephrine (NM), metanephrine (MN), and dopamine (DA) levels were about three times higher in sdhb CRISPants than in control larvae. In the bathing medium, NM and MN were also significantly elevated, along with 3-MT. Complementary metabolic and transcriptomic profiling revealed that sdhb CRISPants exhibit a clear signature of Complex II dysfunction and upregulation of genes involved in the hypoxia response, angiogenesis, stress response, and glycolysis. Our work validates the relevance of CRISPant zebrafish models to study the pathogenicity of PPGL-causing genetic variants in vivo.